Bankfull discharge in mountain streams in the Cauca Region of Colombia - Arbeláez, Ana C., author; Guevara, María Elvira, author; Posada, Lillian, author; González, Luís Jorge, author; Gallardo, Carlos A., author; Colorado State University, publisher (Colorado State University. Libraries, 2007)
A flow considered effective or dominant in the process of stable channel forming, is the bankfull discharge associated to frequency between 1 and 2 years with an average of 1.5 year, according to Dunne and Leopold, 1978. Bankfull discharge or forming discharge is the flow which defines the morphological characteristics of the channel such as bars, meanders and curves. In this article, different approximations for channel forming discharge are explored from the morphological and statistical point of view, in order to establish the frequency of the forming discharge for some rivers in the Andes Region of the Department of Cauca, Colombia.
Hydrology days 2007
AGU hydrology days 2007
2007 annual AGU hydrology days was held at Colorado State University on March 19 - March 21, 2007.